Care Experiences of Older People in the Emergency Department: A Concurrent Mixed-Methods Study. (December 2021) - Mwakilasa, Magreth Thadei; Foley, Conor; O'Carroll, Tracy; Flynn, Rachel; Rohde, Daniela
The growing population of older people has increased demand to meet their complex healthcare needs, including in emergency departments (EDs). This study explored the experiences of people aged 65+ in Irish EDs, involving secondary analysis of quantitative and qualitative data from the 2019 National Inpatient Experience Survey (NIES). Experiences in the ED and overall hospital experiences were dichotomized as poor to fair or good to very good. Logistic regression was used to model quantitative data. Free text comments relating to EDs were thematically analyzed. Of 12, 343 survey participants, 4, 442 (39.9%) were aged 65+ years and used the ED. Longer waiting times, completion of the questionnaire by another person either with or on behalf of the patient, and having both a medical card and private health insurance were predictors of poor to fair ED experiences. Patients aged 85+ years were more likely to report good to very good ED experiences. Poor experiences in the ED were associated with poorer overall hospital experiences (odds ratio [OR]: 2.19, 95% confidence interval [CI]: 1.76 to 2.73, p < .001). Thematic analysis revealed that long waiting times and unpleasant waiting conditions, including lack of communication, privacy, and personal care were important challenges encountered in the ED, with some older patients noting their preference for separate ED services. There is a need to reduce waiting times and integrate user perspectives in the planning, organization, and delivery of ED care to improve experiences and quality of care for a growing older population.